Homofobia entre gays : um estudo sobre a reprodução de discursos e práticas heteronormativas - Figueiredo, Gabriel Henrique Pereira de (2016)
This study aims to understand homophobia amongst gays, considering the reproduction of heteronormative discourse in groups of men who self-identify as gay. Initially, a systematic review of the literature on gay identity in studies on homophobia was held. Then an empirical study has been proposed. It used a form provided virtually answered by 254 men from all over Brazil , who noted the psychosocial characteristics ; representation of gay identities; intragroup relationships; belonging and recognition of gay identity and the internalization of homophobia. Data were analyzed by SPSS Software (IBM SPSS). The main findings showed the importance of the opening of sexuality in the reproduction of prejudice amongst gay men, especially as non - normative gender identities, age, socioeconomic status, beauty standard.